Environmental Management as a Factor in the Safe Management of a Modern Enterprise - USHKULAKOVA, Gulnara; UTALIYEVA, Raikhan; BISSEMBIYEVA, Zhanargul; NAZARENKO, Oxana Vladimirovna; BEKETOVA, Kamar Nazarbekovna; NURGALIYEVA, Almagul Shaimuratovna; AMERZHANOVA, Dinara Amerzhanovna (Journal of Environmental Management and Tourism, 2020)
There is an urgent need to find new ways and approaches to solving environmental problems in production. One of the options for solving such problems is an internationally recognized environmental management. Environmental management at enterprises is a prerequisite for ensuring economic sustainability. The introduction of environmental management provides the company with a tool that enables it to manage all its sources and factors of environmental impact more efficiently and effectively, and to bring its operations in line with various environmental requirements, thus ensuring its environmental and economic sustainability. The article presents a comparative analysis of the economic management system in developed countries and in Kazakhstan. In the context of the global environmental crisis, there is still an irresponsible attitude towards the use of natural resources in developing countries, which is bringing humanity closer to catastrophe; however, environmental management can play an exceptional role in the country's recovery from not only the environmental crisis but also the social and economic crisis.